Developments in the South African credit market and analysis on indebted consumers using NIDS data - Choonoo, Samantha (School of Economics, 2016)
Household debt measures provide vital information regarding society's financial wellbeing. This paper uses a comparative static analysis approach to evaluate total and consumer debt at the household level using two waves of NIDS data relating to the periods 2008 and 2012. The descriptive analysis is based on the share of income servicing debt by various household characteristics while the econometric analysis models the determinants of debt servicing at the household level. The descriptive statistics illustrates the financial vulnerable position of low income households as they spend a proportionally larger share of household income on debt payments and their main sources of credit are from retailers, hire purchase agreements and loan sharks. The OLS and Median Quantile regression results for 2008 and 2012 under total debt analysis indicate a dampening of the negative effect for female, Black, Coloured, no schooling and primary schooling variables; a strengthening of the positive effect for formal house structure made of brick; a dampening of the positive effect for house ownership, post-secondary education, employment and urban variables; and a strengthening of the negative effect associated with government grant income. Results for consumer debt servicing for the same period suggests a narrowing of the gender gap; that lower levels of education are less of a barrier; and that the positive effect associated with urban settlement type has diminished.